Harnessing the Lipogenic Potential of Δ6-Desaturase for Simultaneous Hyperaccumulation of Lipids and Polyunsaturated Fatty Acids in Nannochloropsis oceanica - Yang, Fan; Yuan, Wasiqi; Ma, Yuhan; Balamurugan, Srinivasan; Li, Hong-Ye; Fu, Songling; Wu, Lifang (Frontiers in Marine Science, 2019)
Abstract Burgeoning demand for long-chain polyunsaturated fatty acids (LC-PUFA) due to their established pharmacological and economic significances along with the declining sources of fish urge to explore the sustainable sources of LC-PUFA. Being the predominant LC-PUFA source for marine fishes at the base of the aquatic food web, microalgae has been hailed as a promising natural source for LC-PUFA. However, the potential of algal systems to overproduce LC-PUFA via metabolic engineering is warranted to meet the ever-increasing demand. In this study, we identified and overexpressed Δ6-desaturase, the key enzyme involved in fatty acid desaturation and exemplified its potential on elevating PUFA and lipid content in Nannochloropsis oceanica. Δ6-desaturase overexpression enhanced growth and photosynthetic efficiency. Transgenic cells exhibited a remarkable increase in EPA content and reached up to 652.35 mg/g DW, , the highest EPA production in transgenic N. oceanica by expressing a single key enzyme without impeding growthin a transgenic heterokontgreen alga. Total lipid content was significantly increased by 1.7-fold in the transgenic cell than WT. Together, these findings exemplify a potential candidate for LC-PUFA overproduction and also open a new avenue for sustainable production of microalgal PUFAs.